Changes in values in America and in Colombia (1993-2019) : nationalism, racism, Hispanophobia and sexual permissiveness: this is how 36,516 young students in Latin America think in 1993 and 11,322 in 2019 - Calvo Buezas, Tomás (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Spaniards. These data will be compared with other identical questions that were asked in 1993 to 36,515 Latin American schoolchildren (2.084 of them Colombians) and 5,168 Spanish. The topics deal with nationalisms, xenophobia, racism, negative and positive images about the Spanish colonization in America, and the change of values ​​in America from 1993 to 2019 regarding machismo, sexual morality, religiosity and the degree of happiness.